The Fate of Agriculture in the Semi-arid Regions of Western Iran - A Case Study of the Hamadan Region - Farshad, A; Zinck, J A (Annals of Arid Zone, 2016)
The semi-arid regions of Iran are under increasing pressure to supply the staple grains required by the steadily growing population. The Hamadan plateau, an ancient area at the foot of the Central Zagros mountain (354 m asl at the Alwand peak), was chosen to carry out an analysis of the agricultural systems (traditional vs modem) and to assess their sustainability. Several indicators from the ecosystem and sociosystem were implemented to compare the two systems. like many other places in Iran, also in the Hamadan region agriculture is undergoing a fast change from subsistenance to an advanced level. The resulted changes in social structure, which caused the disruption of the co-evolutionary equilibrium reached over long time by the traditional systems, are analysed.